Regional Fecundity Levels for Colombian Women of Childbearing Age According to Educational Level - Medina Hernández, Edith Johana (Sociedad y Economía, 2012)
Fecundity is a component of the demographic dynamics that determines population growth. In Colombia, like in most Latin American countries, fecundity has significantly decreased in the latest decades, due to the increase of women´s educational levels, among others factors; also, fecundity decrease presents differences by geographical areas of residence.This article presents fecundity estimators, according to educational levels, for women in reproductive age who responded the 2010 Demography and Health National Survey (ENDS 2010). By means of the Brass method, with Coale and Trussell Variant to calculate regional estimators, the article pretends to show similarities and differences in the contribution that these women have made to the process of fecundity transition in Colombia.